Registro geológico holocênico de recifes submersos na plataforma de Abrolhos - Vieira, Laura Silveira (2015)
Coral Reef systems are common features throughout many modern tropical coastal zone and the evidence of their occurrence during different sea levels have been studied worldwide. The Abrolhos Shelf (Brazil) encompasses the most important coral reef system in the South Atlantic showing high levels of endemism, low diversity and unique growth (locally known as “chapeirões”). The reef system along the shelf is characterized by shallow reef arcs parallel to the coast, and “give-up” reefs throughout the north-central and southern shelf. The main objective of this study is to investigate the geological record showing the Late Holocene evolution of two submerged pinnacles in the Abrolhos Shelf. Herein, two submerged pinnacles were drilledwith their tops at 4 and 15 m below sea level, called "Shallow Water Reef" (SW) and "Deep Water Reef" (DW). A total of eight cores were collected. Vertical (top down) and horizontal (perpendicular to the pinnacle wall) cores were recovered, ranging from 0.70 to 2.03 m in length. Significant coralgal framework was observed in the cores (corals such species as Mussismilia harttii., Millepora sp., Siderastrea sp., Porites sp., Favia sp. and Madracis sp.; and coralline algae such species as Hydrolithon sp., Lithophyllum kotschyanum, Lithophyllum sp., Amphiroa sp., Mesophyllum erubescens and Sporolithon episporum). However, we found that by far the most abundant framebuilding component were Schizoporellidae bryozoans. Extensive encrusting bryozoans were identified in all cores comprising between 15 - 52,9% of 2D areas. Bryozoans were most representative in the "DW" cores. Paradoxically, the poor spatial competition of encrusting bryozoans must be the explanation for the bryozoan dominance in the "DW" cores, which hermatypic corals can not develop. Radiocarbon dates indicate that the "DW" reef is older than the "SW" reef as well as higher reef accumulation rates occur in the past thousand years is in the "SW" reef. The results show that the both reefs have been developed in a shallow shelf environment (<30 meters depth)